Lignin-polysaccharide interactions in plant secondary cell walls revealed by solid-state NMR - Xue Kang (Nature Portfolio, 2019)
The interactions of lignin with polysaccharides in plant secondary cell walls are not well understood. Here the authors employ solid-state NMR measurements to analyse intact stems of maize, Arabidopsis, switchgrass and rice and observe that lignin self-aggregates and forms highly hydrophobic microdomains that make extensive surface contacts to xylan.